STRATEGY FOR DEVELOPMENT OF TOURIST VILLAGE IN BALI ISLAND - Widnyana, I Ketut; Karunia, I Putu; Sujana, I Putu (International Journal of Research -GRANTHAALAYAH, 2020)
The Indonesian government is promoting the development of the potential of villages through the tourism village program, but the formation of a tourism village requires prior study to assess its feasibility as a tourism destination. This study aims to analyze the potential and develop strategies for developing Babahan Village in Tabanan Regency, Bali Province as a culture-based tourism village. This research is a qualitative descriptive study which begins with data collection of tourism potential using SWOT analysis and continued with the IFAS-EFAS method. IFAS-EFAS calculation results show the strength factors of the development of Babahan Village as a culture-based ecotourism village are : having a tracking path (0.305), good natural potential (0.305), the existence of Besikalung Temple (0.302), and beautiful rice field views (0.300). SWOT matrix analysis is in Quadrant I (Supporting Aggressive Strategies) with the results of four Strengths-Opportunities (SO) development strategies, namely: a). maintaining and improving the quality of tourist attraction, b). develop and organize the natural potential that exists, c). improve the quality of service to tourists, d). development of tour packages. The conclusion is Babahan Village, Tabanan Regency, Bali has the potential to be developed into a tourism village.